Revolutionary Socialist League contingent - Sahl, Ted (photographer):::Creator::::::::::::
Phtotograph shows marchers with a banner that reads, "From Stone[wall to] San Francisco, It's right to rebel!, Revolutionary Socialist League" at the National March on Washington for Lesbian and Gay Rights.